A simplified method for assessing the dynamic behaviour of a pile in layered saturated soils that considers current scour. (December 2020) - Wang, Lihua; Liu, Chunlin; Wang, Lujun
Abstract: Piles are commonly used in wharfs and offshore platform foundations. The coupled effects of current scour and dynamic load can reduce the non-deformability of a pile-soil system and ultimately lead to structural instability of structures. This paper develops a simplified method to study the dynamic interaction of layered saturated soils and piles under current scour conditions. Fundamental solutions for the dynamic consolidation of layered soil are obtained by the analytical layer element method (ALEM). The pile is modelled as a one-dimensional bar and solved by the finite element method (FEM). By coupling the ALEM and the FEM, solutions for the dynamic behaviour of the pile in soils are obtained while considering current scour. A flexibility matrix that is assembled by fundamental solutions is modified and expanded to match the stiffness matrix of the pile by the simplified method. This approach can solve pile-soil dynamic interaction problems under varied scouring conditions. The influences of scour type, scour depth, excitation frequency and layered property are examined, and the results show that the dynamic behaviour of the pile can be accurately simulated using the simplified method.